PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DENGAN MENGGUNAKAN HANDOUT TERHADAP HASIL BELAJAR SISWA SEKOLAH MENENGAH ATAS NEGERI 1 KAMPAR - Feby Julianti; lisa utami (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
AbstractThis research is based on the low outcomes of class XI students on their chemistry subject. Therefore, the experiment research by pretest and posttest to discover the effect of cooperative learning model of Student Teams Achievement Divisions (STAD) by using Handout toward learning outcomes of State Senior High School 1 Kampar on salt hydrolysis is conducted. The subject of this research is the students of class XI Mia in 2015-2016 year by using 2 classroom samples: XI Mia 1 (exsperiment) dan XI Mia 4 (control). The data was collected by using observation, initial test (homogeneity), final test (pretest and postest), and documentation. To discover the effect of the model on learning outcomes, the formula of Kp is applied. The effect differences are analyzed by t-test sampel related. The analysis result of initial and final data is t-counting = 2.325 and t-table = 1,68 in the significant rate of 5%. The value of t-counting > t-table, therefore, Ho is rejected and Ha is accepted. This shows that there is the effect of cooperative learning model of Student Teams Achievement Divisions (STAD) by using handout toward learning outcomes of State Senior High School 1 Kampar on salt hydrolysis by the effect as much as 7.8%.  Key words:      Learning outcomes, model learning model of STAD, salt hydrolysis